Children’s awareness about collection and recycling garbage with the aid of robotics - Santos, Tatiana Nilson dos; Pozzebon, Eliane; Frigo, Luciana Bolan (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The objective of this paper is to present the results of activities about collection and recycling of garbage to elementary school children assisted by robotics and conduct a discussion on the use of both educational robotics, as technology itself, in the classroom. The activities were conducted through a project of the Federal University of [omitted in this version], participated in this project where children aged 8-10 years. Activities in tablets, robots, colored balls, recyclable waste and garbage cans were used. It was noticed that the inclusion of technology in the classroom brings great benefits in learning of these students. Bring to the classroom tools/materials of the day-to-day student made him feel more at ease in learning, and show more interest in studying content where it can opine and assimilate with their reality.